Comparison of Diagnostic Cytomorphology of Natural Killer/T-Cell Lymphoma (Nasal Type) in Conventional Smears, Liquid-Based Preparations, and Histopathology - Chih-Yi Liu; Hui-Chih Tsai (Case Reports in Pathology)
Natural killer (NK)/T-cell lymphoma is formally referred to as extranodal NK/T-cell lymphoma, nasal type (ENKTCL), in the 2008 and 2016 World Health Organization (WHO) classifications. NK/T-cell lymphoma, nasal type, is a rare but clinically important lymphoid neoplasm. It is the predominant type of extranodal lymphoma associated with the Epstein–Barr virus (EBV). NK/T-cell lymphoma is marked by a wide cytomorphological spectrum. The cytological findings may be so subtle that NK/T-cell lymphoma could possibly be easily overlooked. Here, we report a case of NK/T-cell lymphoma involving the sinonasal region with lymph node involvement. Fine needle aspiration of the neck lymph node and punch biopsy of the nasal mucosa were performed. The diagnosis of NK/T-cell lymphoma was confirmed based on pathological and immunohistochemical analyses, as well as in situ hybridization for EBV-encoded mRNA (EBER). The present case report underlines the importance of prompt clinicopathological assessment in suspected cases. The comparison of cytomorphologic features of NK/T-cell lymphoma in various specimens is presented.